0226 Initiatives To Enhance Interprofessional Learning And Team Behaviours Through Student-to-student Feedback And Assessment In An Informal Environment. (1st November 2014) - Kwan, Jennifer; Hong, Jennifer; Samani, Krupa; Mullins, Sophie; Saibudeen, Aashima; Stuttard, Matthew; Anderson, Elizabeth
Abstract : Background: Recent emphasis in medical education has focussed on interprofessional learning and teaching, training, and appraisal skills. 1 Learning with other students enhances communication skills, develops professional respect for colleagues and improves team performance. 2 All professions need to work together and be able to professionally challenge each other, learning to receive positive and negative feedback. We set up a scheme to provide interprofessional students with the skills of teaching and learning in feedback and assessment. Methodology: A one-day conference was organised, bringing together students and academics from University of Leicester and De Montfort University in a range of backgrounds: medicine, nursing, physiotherapy, speech and language therapy, pharmacy. Experienced lecturers agreed to add content on interprofessional communication, assessment and feedback. The student team designed a range of activities supported by the JASME Teaching Toolkit, to replicate patient management/discharge, and several skills-based activities 3 to apply the morning theory-based lectures, so students could practise and receive real-time feedback from each other. The student team organised the conference day. Outcomes: Out of 23 reserved places, 15 attended. 14 recorded an improvement in skills on giving and receiving feedback; 13 rated the activities as very good/excellent as they allowed for collaborative practice and insight into the health disciplines. Delegates particularly praised the feedback element of the sessions and everyone concluded this was an event they would recommend to colleagues. Potential impact: Students appreciated the friendly environment to foster interprofessional collaboration and an insight into holistic care. Most recognised that giving and receiving feedback was challenging, but this was a safe place to practise. The experience provided them more empathy towards teachers and acknowledgement how difficult giving negative criticism can be. We aim to improve the event this year by gaining official recognition from the university and involving more interprofessional student groups in writing the simulations. References: General Medical Council. Good Medical Practice. London: GMC; 2009 Thistlethwaite J. Interprofessional education: a review of context, learning and the research agenda. Med Educ 2012 Jan;46(1):58–70 Miller GE. The assessment of clinical skills/competence/performance. Acad Med 1990 Sep;65(9 Suppl):S63–7